2016
DOI: 10.22456/1679-9216.80900
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Disease-free Interval of Cats with Mammary Carcinoma Treated with Chain Mastectomy

Abstract: Background: Mammary tumors are extremely common in cats and have high metastatic rates with poor prognosis. The main objective of the present study was to evaluate the disease free interval and survival in cats undergoing radical mastectomy as sole therapy.Materials, Methods & Results: Twenty cats with mammary tumors and no evidence of distant metastasis were studied. General health and concomitant diseases were assessed by clinical and hematological examination. Thoracic radiographs and abdominal ultrason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 8 publications
(1 reference statement)
1
9
1
10
Order By: Relevance
“…In Brazil, a breed predisposition was not observed (CUNHA et al, 2016), as opposed to a previous international study that found Siamese cats to be more predisposed to mammary tumors (SORENMO et al, 2013). This fact is likely due to the domestic feline population in Brazil being predominantly composed of mongrel cats (CUNHA et al, 2016).…”
Section: Epidemiology and Risk Factorscontrasting
confidence: 63%
See 1 more Smart Citation
“…In Brazil, a breed predisposition was not observed (CUNHA et al, 2016), as opposed to a previous international study that found Siamese cats to be more predisposed to mammary tumors (SORENMO et al, 2013). This fact is likely due to the domestic feline population in Brazil being predominantly composed of mongrel cats (CUNHA et al, 2016).…”
Section: Epidemiology and Risk Factorscontrasting
confidence: 63%
“…The regional, axillary and inguinal, lymph nodes, even if not clinically altered, should be excised at the time of mastectomy due to the high incidence of regional metastases (CUNHA et al, 2016). For the axillary lymph node lymphadenectomy (Figure 4), Patent Blue dye (2.5%) is applied intradermally at a dose of 2 mg/kg, without exceeding the volume of 1 ml per patient, to facilitate the identification and removal of the lymphatic tissue.…”
Section: Sentinel Lymph Nodementioning
confidence: 99%
“…Animais da raça siamesa apresentam maior chance do desenvolvimento precoce da doença, por volta dos 9 anos de idade, além de ser uma raça mais predisposta quando comparada às demais (ZAPPULLI et al, 2015). No entanto, um estudo realizado no Brasil não demonstrou esta predisposição racial, onde a maior parte dos animais acometidos não apresentavam raça definida (CUNHA et al, 2016).…”
Section: Lista De Quadrosunclassified
“…No entanto, a sobrevida destes animais pode variar de alguns meses até um ano, com uma variação média de 7,7 até 12 meses (OVERLEY et al, 2005;CUNHA et al, 2016…”
Section: Introductionunclassified
“…frequente nesta espécie(TOGNI et al, 2013). Alguns estudos estabelecem a raça Siamesa como predisponente ao câncer mamário(ZAPPULLI et al, 2005), porém outros não demonstram esta relação, talvez pela heterogeneidade de raças na população estudada(CUNHA et al, 2016). Os animais mais acometidos…”
unclassified